Functional and quality of life outcomes after partial glossectomy: a multi-institutional longitudinal study of the head and neck research network - Agnieszka Dzioba; Daniel Aalto; Georgina Papadopoulos-Nydam; Hadi Seikaly; Jana Rieger; Johan Wolfaardt; Martin Osswald; Jeffrey R. Harris; Daniel A. O’Connell; Cathy Lazarus; Mark Urken; Ilya Likhterov; et al. (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background While aggressive treatment for oral cancer may optimize survival, decrements in speech and swallowing function and quality of life often result. This exploratory study investigated how patients recover their communicative function, swallowing ability, and quality of life after primary surgery [with or without adjuvant (chemo)radiation therapy] for tongue cancer over the course of the first year post-operation. Methods Patients treated for oral cancer at three institutions (University of Alberta Hospital, Mount Sinai Beth Israel Medical Center, and Turku University Hospital) were administered patient-reported outcomes assessing speech [Speech Handicap Index (SHI)], swallowing [(M.D. Anderson Dysphagia Inventory (MDADI)] and quality of life [European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Head and Neck Module (EORTC-H&N35)]. Outcome measures were completed pre-operatively and at 1-, 6-, and 12-months post-operatively. Results One hundred and seventeen patients undergoing partial glossectomy with reconstruction participated in this study. Results indicated no significant differences in swallowing function (MDADI and EORTC-H&N35 subscales) between baseline and 6 months post-surgery and no significant differences in speech function (SHI subscales) between baseline and 1 year post-surgery. Most quality of life domains (EORTC-H&N35 subscales) returned to baseline levels by 1 year post-operation, while difficulties with dry mouth and sticky saliva persisted. A clear time trend of adjuvant (chemo)radiation therapy negatively affecting dry mouth scores over time was identified in this study, while negative independent effects of chemoradiation on MDADI swallowing, and EORTC-H&N35 swallowing, eating, and opening mouth subscales were found. Conclusions Assessment time influenced patient-reported speech, swallowing, and quality of life outcomes, while treatment (by time) effects were found for only swallowing and quality of life outcomes. Results of the present study will help guide clinical care and will be useful for patient counseling on expected short and long-term functional and quality of life outcomes of surgical and adjuvant treatment for oral cavity cancer.